Módulo de peso para sl2(C) - Igor Martins Silva (2021)
In this manuscript, we will study the Lie algebra sl2(C) and certain classes of modules over this Lie algebra. In particular, we classify all simple weight sl2(C)-modules and describe several full subcategories of the category of weight sl2(C)-modules.